Portal dosimetry in wedged beams. (8th May 2015) - Spreeuw, Hanno; Rozendaal, Roel; Camargo, Priscilla; Mans, Anton; Wendling, Markus; Olaciregui‐Ruiz, Igor; Sonke, Jan‐Jakob; Van Herk, Marcel; Mijnheer, Ben
Abstract : Portal dosimetry using electronic portal imaging devices (EPIDs) is often applied to verify high‐energy photon beam treatments. Due to the change in photon energy spectrum, the resulting dose values are, however, not very accurate in the case of wedged beams if the pixel‐to‐dose conversion for the situation without wedge is used. A possible solution would be to consider a wedged beam as another photon beam quality requiring separate beam modeling of the dose calculation algorithm. The aim of this study was to investigate a more practical solution: to make aSi EPID‐based dosimetry models also applicable for wedged beams without an extra commissioning effort of the parameters of the model. For this purpose two energy‐dependent wedge multiplication factors have been introduced to be applied for portal images taken with and without a patient/phantom in the beam. These wedge multiplication factors were derived from EPID and ionization chamber measurements at the EPID level for wedged and nonwedged beams, both with and without a polystyrene slab phantom in the beam. This method was verified for an EPID dosimetry model used for wedged beams at three photon beam energies (6, 10, and 18 MV) by comparing dose values reconstructed in a phantom with data provided by a treatment planning system (TPS), as a function of field size, depth, and off‐axis distance. Generally good agreement, within 2%, was observed for depths between dose maximum and 15 cm. Applying the new model to EPID dose measurements performed during ten breast cancer patient treatments with wedged 6 MV photon beams showed that the average isocenter underdosage of 5.3% was reduced to 0.4%. Gamma‐evaluation (global 3 % / 3   mm ) of these in vivo data showed an increase in percentage of points with γ ≤ 1 from 60.2% to 87.4%, while γ mean reduced from 1.01 to 0.55. It can be concluded that, for wedged beams, the multiplication of EPID pixel values with an energy‐dependent correction factor provides good agreement between dose values determined by an EPID and a TPS, indicating the usefulness of such a practical solution. PACS numbers: 87.55.km, 87.55.kd, 87.55.Qr, 87.56a.ng